Strategy Development Process in Higher Education: The Case of Marmara University - GÜLLÜOĞLU, ARİF NİHAT; ÖNCER, AYLA ZEHRA; YILDIZ ŞEN, MÜGE LEYLA; BAKOĞLU, REFİKA (ELSEVIER SCIENCE BV, 2016)
Strategic planning in higher education has become one of the most important factors of today's education system. State of the Republic of Turkey, which is aware of importance of this trend in the world, made the preparation and implementation of five-year strategic plans mandatory for higher education institutions. However, when examining the strategic plans made by universities in Turkey in general, it draws attention that strategy development techniques are not used in development processes. Strategies at different levels in universities are not taken in consideration, and strategies are not determined by high participation and not formed and implemented in a conscious way. Marmara University has developed a different and unique approach by considering these facts when doing researches to develop strategies to be effective in the next five-year period. In this notification, it is aimed to reveal strategical approach developed exclusive to universities in 2017-2021 strategic plan of Marmara University, and strategy development process model formed for the purpose of being internalized of strategy in institution. In this respect, in study; it is mentioned how participation of academic and administrative personnel is provided, in which way it is focused on creating value for all stakeholders, how internal and external environment analysis are made with which scientific research projects and how corporate learning is supported in every stage of the process. This paper tries to highlight a case from Marmara University's strategy development process indicating how strategic plan on the paper can be changed into internalized strategy creating change, momentum and dynamism trough the both implementation of a new approach to strategy and strategy development process. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Strategy; strategy development; university